Understanding Agriculture-Industry Inter-Linkages For Agrarian Development: Empirical Evidence From India - Mehra, Sahil (H. : ĐHKT, 2020)
Indian agriculture sector suffers from a number of institutional, socio and economic problems. Structural change posits for the economy to move away from agriculture sector and towards more advanced industrial and services sector. With nearly 47% of India‟s population stuck in agriculture, structural change seems to be a far cry. The population is stuck, as according to a survey, 40% of people in agriculture wanted to leave agriculture activity but could not (Situation Assessment Survey, NSSO 59Th round, 2003). The alternate avenues in the economy are too few. The falling share of manufacturing sector, and burgeoning informal sector provide very few opportunities for people to move away from the agriculture sector.